Power-optimized stiffness and nonlinear position control of an actuator with Variable Torsion Stiffness - Wojtusch, J.; Schuy, J.; Strah, B.; Rinderknecht, S.; Stryk, O. V.; Beckerle, Philipp (2013 IEEE/ASME International Conference on Advanced Intelligent Mechatronics: Mechatronics for Human Wellbeing, AIM 2013, 2013)
Introducing compliant actuation to robotic joints is an approach to ensure safety in closer human-machine interaction. Further, the possibility to adjust stiffness can be benificial considering energy storage and the power consumption required to track certain trajectories. The subject of this paper is the stiffness and position control of the Variable Torsion Stiffness (VTS) actuator for application in compliant robotic joints. For the realization of a variable rotational stiffness, the active length of a torsional elastic element in serial configuration between drive and link is adjusted in VTS. After the deduction of an extended drive train model, this paper gives an advanced power analysis clarifying power-optimal settings from previous basic models and identifying additional settings that allow for a more versatile operation. Based on these results that can be generalized to other variable elastic actuator concepts, an optimized strategy for setting stiffness is determined considering the whole system dynamics including natural frequencies as well as antiresonance effects. For position control of VTS in a prototypical implementation, a nonlinear position controller is designed by means of feedback linearization. Although the system is modified significantly by changing drive train stiffness, the stiffness adaptation of the controller ensures the required tracking performance. © 2013 IEEE.
CRIS-Team Scopus Importer:2021-09-24